For a literature of the interdependance. Literature and politic renewals in black Africa, from Mongo Beti - (:unkn) unknown (My University, 2009)
The links between literature and african politic seem to be so close that they concentrated the problematics and the evolutions of artistic field. According to Mongo Beti, the relation is preponderant, whereas Alain Mabanckou asserts that this closeness is a possibility. Between these generations, it exists both an esthetical and ideological change: the crossing from delinking to an interdependant regime. The writers focus on the useful of the form in ordrer to underline the meaning. The politic of literature follows the contours of the world and its entrance in the era of the Poetic of Relation.
Keywords: African Research